RECONSTRUCTING THE EPISTEMOLOGY OF ISLAMIC ECONOMICS AND EDUCATION IN THE ERA OF ARTIFICIAL INTELLIGENCE AND THE DIGITAL ECONOMY - Ruslan, Murniati; Ubay, Ubay; Musyahidah, Sitti (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to explore the reconstruction of Islamic economics and education epistemology in the face of technological advances, particularly artificial intelligence (AI) and the digital economy, using a Systematic Literature Review (SLR) approach. This method was chosen to obtain a comprehensive mapping of scientific discourse developments, identify research gaps, and synthesize findings from primary literature indexed in the Scopus database for the period 2019–2024. The research is exploratory and qualitative in nature, employing documentary and narrative analysis of articles relevant to the topic of Islamic economic epistemology and its relationship with AI, the digital economy, and Islamic ethics in technology. The search strategy uses a combination of Boolean keywords such as “Islamic economics” AND ‘epistemology’ AND (“artificial intelligence” OR “digital economy”), supported by the Google Scholar and ScienceDirect databases. The findings indicate that the integration of AI and the digital economy into Islamic economic systems and education requires a profound epistemological reconstruction to ensure that fundamental values such as justice, moral responsibility, and equality are upheld. AI plays a dual role as an instrument of efficiency and a potential source of ethical disruption, while digitalization drives the reinterpretation of traditional Islamic economic values and practices. Technologies like blockchain offer transparency but also raise ethical dilemmas related to privacy and Sharia compliance. Current literature still shows limitations in terms of a comprehensive conceptual framework and a lack of interdisciplinary empirical research. Therefore, a systematic and ethical approach is needed to harmonize technological innovation with Islamic principles, as well as further research examining the impact of AI on core concepts such as zakat distribution and ethical accountability in Islamic economics to ensure their relevance and adaptability in the digital age.